Determination of the volumetric shrinkage in jatropha seeds during drying - doi: 10.4025/actasciagron.v34i3.14402 - Valdiney Cambuy Siqueira; Osvaldo Resende; Tarcísio Honório Chaves (Acta Scientiarum. Agronomy, 2011)
The objective of this study was to determine the geometric diameter of volumetric shrinkage in Jatropha seeds subjected to drying under six air conditions and to fit different mathematical models to the experimental values. Seeds with an approximate initial moisture content of 0.61 kgw kgdm-1 (kilogram of water per kilogram of dry matter) were dried in a convection oven at temperatures of 36, 45, 60, 75, 90, and 105°C until they reached a moisture content of 0.11 ± 0.006 kgw kgdm-1. The experimental data were fitted to five mathematical models used to represent volumetric shrinkage in agricultural products. The models were analyzed using the coefficient of determination, chi-square, mean relative error, mean estimated error, and residual distribution. Geometric diameter data were subjected to regression analysis by adopting a 1% level of significance. It was concluded that moisture content and drying temperature influence volumetric shrinkage in Jatropha seeds, a phenomenon satisfactorily described by the Polynomial equation, where the geometric diameter linearly decreased with a reduction of the moisture content, regardless of the drying conditions.